Biofertilizers in production of vine Isabel - Silva, Francisca Lacerda da; Lima, Alex Serafim de; Santos, Jéssica da Mota; Alves, Jackson de Mesquita; Sousa, Caio da Silva; Santos, José Geraldo Rodrigues dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The "Isabel" vine is one of the most important crops both for the agricultural sector and for subsistence of small families. The bovine biofertilizer appears as an alternative to replace the excessive use of chemical fertilizers in small properties, where it can be used in agricultural crops providing quality and quantity aspects, acting positively in the soil-water-plant system. In this perspective, the objective was to evaluate the production of Isabel grape fruits, fertilized with types and doses of bovine biofertilizer, during the second productive cycle. The experiment consisted of a randomized block design, with factorial 5 x 8, referring to five types of biofertilizer: (B1 = bovine manure, B2 = B1 + MB4 rock meal, B3 = B2 + legume (Vigna unguiculate L. Walp.), B4 = B2 + wood ash and B5 = B3 + wood ash) and 8 doses of biofertilizer (D1 = 0; D2 = 0.35; D3 = 0.7; D4 = 1.05; D5 = 1.4; D6 = 1.75; D7 = 2.1 and D8 = 2.45 L/plant/time), applied every 2 months. The types of biofertilizer B1, B2, B4 and B5 exert significant values in production, except for quality. The use of biofertilizer applied 1,2 L/plant/time provides greater productive efficiency of Isabel vine fruits in types B1, B2, B4 and B5, except for ºBrix and acidity. The application of different types of bovine biofertilizer associated to optimal dosages leads to plants with high productive potential.